2020
DOI: 10.3390/ijms21093327
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Enhances MAL-PDT Cytotoxic Effect on PDT-Resistant Skin Cancer Squamous Cells

Abstract: Photodynamic therapy (PDT) has been used to treat certain types of non-melanoma skin cancer with promising results. However, some skin lesions have not fully responded to this treatment, suggesting a potential PDT-resistant phenotype. Therefore, novel therapeutic alternatives must be identified that improve PDT in resistant skin cancer. In this study, we analyzed the cell viability, intracellular protoporphyrin IX (PpIX) content and subcellular localization, proliferation profile, cell death, reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…17,37 Vitamin E (α-tocopherol) in combination with PDT, increased PDT cytotoxicity, in a concentration and incubation timedependent manner. 15 Recently, León et al 18 reported that epigallocatechin gallate catechin enhanced MAL-PDT in resistant skin cancer squamous cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,37 Vitamin E (α-tocopherol) in combination with PDT, increased PDT cytotoxicity, in a concentration and incubation timedependent manner. 15 Recently, León et al 18 reported that epigallocatechin gallate catechin enhanced MAL-PDT in resistant skin cancer squamous cells.…”
Section: Discussionmentioning
confidence: 99%
“…Results have been promising, as enhancement of PDT efficacy has been shown by the addition of an antioxidant agent. [13][14][15][16][17][18][19][20] This study aimed to evaluate the enhancement of PDT efficacy through modulation of the intracellular ROS levels by using natural polyphenols. Polyphenols are powerful natural antioxidants that, like any antioxidant, can exert pro-oxidant activities under certain conditions, mainly depending on their concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, free radical chemical scavengers can neutralize the generated ROS, minimizing the adverse effect of oxidative damage caused in nontarget healthy tissues. Various antioxidant agents, such as cinnamaldehyde, ascorbate, polyphenols, and epigallocatechin gallate, have been investigated in combination with PDT. These studies have confirmed and claimed that using antioxidant inhibition along with PDT could be a promising approach to potentiate ROS-mediated anticancer treatments’ therapeutic efficacy and reduce side effects. The most effective radical scavengers are phenolic (ArOH) antioxidants, which could control the auto-oxidation process by donating a H atom (from OH groups) to peroxy radicals (RO 2 · ) and converting them into hydroperoxide. The antioxidant-generated phenoxy radical reacts in different ways with other proxy radicals and terminates the propagation of free radical species by forming nonradical products . Recently, a photosensitizing chitosan-based antioxidant hydrogel using tannic acid as an antioxidant cross-linking agent has been reported to effectively utilize a combination of free radical scavenging and pro-oxidant activities.…”
Section: Introductionmentioning
confidence: 95%
“…EGCG, a nontoxic catechin found in green tea ( Camellia sinensis ), has an established place in preclinical research on cancer prevention and treatment generally, with increasing clinical applications [ 174 , 175 ]. A MAL-PDT-resistant cSCC cell model was developed showing reduced PpIX and ROS generation, but these PDT-resistant cells were resensitized by EGCG, indicating its potential as an adjuvant to MAL-PDT [ 176 ]. In other cancers, EGCG has been shown to reduce cell growth better when combined with PDT compared with either treatment separately [ 177 ].…”
Section: Potential Improvements In Topical Pdtmentioning
confidence: 99%